2018
DOI: 10.5603/fm.a2017.0065
|View full text |Cite
|
Sign up to set email alerts
|

A rare vascular anomaly in the form of double left brachiocephalic vein detected incidentally during cardiac implantable electronic device (CIED) placement

Abstract: The growing number of transvenous cardiac implantable electronic device (CIED)implantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…In the few reported cases, the anterior LBV superior to the aortic arch is usually present but multiple variants of the course of the other LBV have been described such as retro aortic course 3 as in our case, retroesophageal, 4 and anterior to the aortic arch parallel to the normal LBV 2 …”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In the few reported cases, the anterior LBV superior to the aortic arch is usually present but multiple variants of the course of the other LBV have been described such as retro aortic course 3 as in our case, retroesophageal, 4 and anterior to the aortic arch parallel to the normal LBV 2 …”
Section: Discussionmentioning
confidence: 50%
“…Chen et al suggested the existence of a double interprecardinal anastomoses in embryonic life, a cephalic ventral, and another caudal dorsal with regression of the dorsal component and the ventral from the normal LBV but the additional branch might be caused by the remnants of the dorsal anastomosis. 1In the few reported cases, the anterior LBV superior to the aortic arch is usually present but multiple variants of the course of the other LBV have been described such as retro aortic course 3 as in our case, retroesophageal,4 and anterior to the aortic arch parallel to the normal LBV 2. The diagnosis of double LBVs can be challenging using echocardiography or CT.…”
mentioning
confidence: 70%
See 3 more Smart Citations